Adaptation in the Anthropocene: issues of justice in national adaptation programmes of action - White, Abbie, author (Colorado State University. Libraries, 2017)
Adaptation is and will continue to be an opportunity to tackle the effects of climate change with the potential to address or exacerbate issues of justice. Adaptation activities and governance can support or derail just transitions and just futures. This is of particular importance for vulnerable communities, who contribute less to the drivers of climate change, but are burdened with more of the effects. In recognition of global inequalities and the specific vulnerabilities of least developed countries (LDCs), the United Nations Framework Convention on Climate Change (UNFCCC) developed National Adaptation Programmes of Action (NAPAs). NAPAs are a way for LDCs to determine and communicate their urgent adaptation needs and provide an avenue for adaptation activities to be funded. This paper analyses the considerations of justice that are inscribed in NAPA reports submitted to the UNFCCC. In doing so, it will examine issues of distributive justice and procedural justice embedded in the NAPA reports and preparation process. While the broad idea of NAPAs addresses issues of inequality and justice at a global scale, by applying to LDCs, this paper questions whether these rhetorical commitments to justice are actualised in the reports and whether a commitment to justice is carried through to the most vulnerable communities within countries. NAPAs can be seen as a governance tool that in theory can address issues of justice. Fair and transparent governance, planning and implementation of adaptation measures is necessary to avoid exacerbating existing inequalities and the creation of new injustices within and between current and future generations. This paper aims to contribute to this symposium by providing insights into the justice considerations in NAPAs.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: climate justice; United Nations Framework Convention on Climate Change; UNFCCC; least developed countries; adaptation; mitigation